Diversion Colitis and Probiotic Stimulation: Effects of Bowel Stimulation Prior to Ileostomy Closure - Rodríguez-Padilla, Ángela; Morales-Martín, Germán; Pérez-Quintero, Rocío; Rada-Morgades, Ricardo; Gómez-Salgado, Juan; Ruiz-Frutos, Carlos (Frontiers in Medicine, 2021)
Background: Diversion colitis is a non-specific inflammation of a defunctionalised segment of the colon after a temporary stoma has been performed. This inflammation is associated with a change in the colonic flora. Aim: To evaluate the efficacy and safety of preoperative stimulation of the efferent loop with probiotics prior to closure of the protective ileostomy in patients operated on colorectal carcinoma and its effect on diversion colitis. A prospective, randomised, double-blind, controlled study is carried out. Methods: Patients who underwent surgery for colorectal carcinoma with protective ileostomy pending reconstructive surgery and with diversion colitis as diagnosis are included. Randomised and divided into two groups. Histological and endoscopic changes were evaluated after stimulation, after restorative surgery and during the short-term follow-up after surgery. Results: Patients in CG were distributed according to the endoscopic index of severity in pre-stimulation/post-stimulation as follows: severe n = 9/9 (25.7%), moderate n = 23/23 (65.7%), and mild n = 3/3 (8.6%); compared to the distribution in SG, severe n = 9/0 (26.5/0%), moderate n = 23/3 (67.6/8.8%), mild n = 2/19 (5.9/55.9%) and normal colonoscopy in 0/12 patients (0/35.3%). Conclusion: Probiotic stimulation of the efferent loop is a safe and effective method, managing to reduce both macroscopic and microscopic colitis, as well as a decrease in symptoms in the short term after reconstructive surgery.